ANALISIS LINGKUNGAN KERJA DALAM MENINGKATKAN KEPUASAN KERJA PEGAWAI PADA KANTOR POS INDONESIA KOTA TANGERANG SELATAN - Nurul Rahmadhania; Putri Roni Fadli (Journal of Research and Publication Innovation, 2025)
This study aims to find out and analyze in depth the work environment and job satisfaction as well as how effective the work environment is in increasing employee job satisfaction at the Indonesian Post Office in South Tangerang City. A conducive work environment is believed to be able to increase employee motivation, productivity, and welfare so that it has a positive impact on job satisfaction. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, observations, and documentation of employees of the Indonesian Post Office in South Tangerang City. The results of the study show that the work environment at the Indonesian Post Office in South Tangerang City faces obstacles such as inadequate physical facilities, noise, and suboptimal air circulation, which has an impact on employee comfort and productivity. Although the relationship between employees and superiors is good, employee job satisfaction is not optimal due to the workload that is not in accordance with interests and late overtime payments. However, the work environment is considered quite effective in increasing job satisfaction thanks to harmonious working relationships and management support. To maximize job satisfaction, companies need to improve physical facilities and address issues related to overtime pay and workload. This improvement is expected to increase job satisfaction in a sustainable manner and encourage employee loyalty and performance. This study recommends that the management of the Indonesian Post Office in South Tangerang City continue to evaluate and improve aspects of the work environment to create a better working atmosphere and increase employee job satisfaction in a sustainable manner for the welfare of employees and organizational success.